OLD PROHIBITIONS AND NEW FACES: RIBA, GHARAR, AND MAYSIR IN CONTEMPORARY DIGITAL FINANCE - Hoirul Anam; Muhammad Irsyad Elfin Mujtaba; Pavita Aqila Zeba; Selviana Anggraeni (International Conference on Humanity Education and Society (ICHES), 2026)
The rapid development of the digital economy has introduced financial innovations that enhance efficiency while simultaneously challenging the implementation of Sharia principles. Practices of riba, gharar, and maysir no longer appear in explicit traditional forms but are embedded in modern instruments such as interest-based online lending, conventional insurance, binary options, and speculative cryptocurrency trading. This study examines the continued relevance of these prohibitions in contemporary finance and analyzes the transformation of risks within modern contractual arrangements. Using a qualitative descriptive-analytical approach, the research draws upon classical fiqh literature and contemporary scholarly works. The findings reveal that although transaction mechanisms have evolved through digitalization, the substantive objectives of Sharia prohibitions remain consistent: preventing injustice, excessive speculation, and economic exploitation. Modern financial practices involving interest, high uncertainty, and speculative elements essentially replicate classical prohibitions in new forms. Therefore, strengthening Sharia-compliant financial innovation, adaptive regulation, and public financial literacy is essential to uphold justice, transparency, and risk-sharing in the digital financial system.